2014
DOI: 10.3109/13880209.2014.936471
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and antioxidant properties of phenolic compounds fromTagetes patulaflower

Abstract: Compound 2 from T. patula flower exhibited both growth inhibitory and cytotoxic properties while 1 and 3 were only growth inhibitory against HeLa. 1-3 also displayed antioxidant properties implying its probable role in growth inhibition/cytotoxic action. The present study provides scientific evidence for the use of T. patula flower in cancer treatment by traditional healer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 56 publications
1
24
0
1
Order By: Relevance
“…Some studies showed that luteolin and kaempferol derivatives exhibit cytotoxic activity. [ ][ ] Patulitrin showed growth inhibitory effect against HeLa cells …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies showed that luteolin and kaempferol derivatives exhibit cytotoxic activity. [ ][ ] Patulitrin showed growth inhibitory effect against HeLa cells …”
Section: Resultsmentioning
confidence: 99%
“…[61] [62] Patulitrin showed growth inhibitory effect against HeLa cells. [64] Conclusions Centaurea ragusina flower and herba AE showed good cytotoxic activity against human bladder (T24) and human glioblastomma (A1235) cancer cell lines. Apparent cytotoxic activity of tested C. ragusina AE can be connected with chemical composition of both tested extracts.…”
Section: Antiproliferative Activity Of Centaurea Ragusina Aqueous Extmentioning
confidence: 98%
“…The assignment of 1 H-NMR and 13 C-NMR chemical shifts of the core portion of compounds 1-5 was carried out by 2D NMR experiments ( Table 2). The spectra exhibited the characteristic signals of amide, O-bearing methylene and methine groups, nitrogenous methine, and two unbranched long chain methylene envelops with one double bond character ( Table 2, Figure 1).…”
Section: Compound Isolation and Characterizationmentioning
confidence: 99%
“…Another insoluble fraction, JYM-PV155AIN was evaluated through EI-MS, HR-EI-MS, 1 H-NMR and 13 C-NMR spectra which disclosed its structure as β-sitosterol glucoside (6; Figure 1) whereas, JYM-PV157AIN was found to be a mixture of 6 and ceramides (1 -5). β-Sitosterol glucoside (6) was identified by 1 H-and 13 C-NMR spectroscopy ((D 5 )pyridine) and comparison with previously published data.…”
Section: Compound Isolation and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation